Graphene nanoribbons formed by a sonochemical graphene unzipping using flavin mononucleotide as a template. (January 2015) - Yoon, Woojin; Lee, Yonggeun; Jang, Hongje; Jang, Myungsu; Kim, Jin Sung; Lee, Hee Sung; Im, Seongil; Boo, Doo Wan; Park, Jiwoong; Ju, Sang-Yong
Abstract: When the width of a graphene nanoribbon (GNR) is only a few nanometers, it possesses semiconducting properties that enable various high-end electronic applications. In this study, we report that the dense and stable dispersion of a natural graphite formed using flavin mononucleotide (FMN) as a surfactant produces GNRs as small as 10 nm in width. High-resolution transmission electron microscopy reveals GNRs with various widths, along with a graphene flake containing straight-edged GNRs and cuts, depending on substrate treatments. Such nanoribbon formation originates from sonochemical graphene unzipping with a one-dimensional FMN supramolecular ribbon as a template. Raman spectroscopy demonstrates the universal intensity ratio of D over D′ bands near 4, supporting formation of continuous edge defect. Thermal annealing enhances the optical contrast and van der Waals interactions of the graphene film, resulting in increased conductivity compared to the as-prepared graphene film, which is also better than that of reduced graphene oxide.